ChemInform Abstract: Palladium‐Catalyzed Ring‐Opening Alkynylation of Cyclopropenones. Issue 49 (3rd December 2013) - Matsuda, Takanori; Sakurai, Yusuke
Abstract Propargylic esters (VI) bearing an aryl or alkenyl group at the propargylic position exclusively afford 4‐methylenecyclopentenones via [3 + 2] annulation.